2017
DOI: 10.29121/granthaalayah.v5.i2.2017.1704
|View full text |Cite
|
Sign up to set email alerts
|

Biometric Attendance Monitoring System of Cagayan State University – Lasam Campus, Philippines

Abstract: The study aimed to develop a fully customized Biometric Attendance Monitoring System (BAMS) of Cagayan State University – Lasam Campus, Philippines (CSU - Lasam) using biometric fingerprint reader to facilitate the monitoring of employees’ attendance. This study followed the framework of Design Science Research for Information Systems, thus, the researcher identified the problems and issues encountered in the monitoring of attendance, defined the objectives of the study, designed and developed the system, depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Moreover, client satisfaction of the implementation of ARTA in SLSU-Tomas Oppus Campus in Leyte by frontline offices supports the findings above (Maggay, 2014) [16]. These are also affirmed by Llanera (2016) [13] who measured the level of student satisfaction of the frontline services of CAPSU Satellite Colleges and found the level of student satisfaction very satisfactory.…”
Section: Level Of Client Satisfactionsupporting
confidence: 66%
“…Moreover, client satisfaction of the implementation of ARTA in SLSU-Tomas Oppus Campus in Leyte by frontline offices supports the findings above (Maggay, 2014) [16]. These are also affirmed by Llanera (2016) [13] who measured the level of student satisfaction of the frontline services of CAPSU Satellite Colleges and found the level of student satisfaction very satisfactory.…”
Section: Level Of Client Satisfactionsupporting
confidence: 66%
“…EBEEC 2018 [4] asserted that the implementation of an electronic biometric-based method of attendance management system for non-academic staffs in IBBU Lapai will greatly assist IBB University Lapai in improving the net productivity of the institution and there by prevents time-consuming processes in attendance registering. [5] implemented the Biometric Attendance Monitoring System (BAMS) in The Cagayan State University -Lasam Campus, Philippines (CSU -Lasam). It is revealed that BAMS greatly contributes in providing employees' ease and improving work values.…”
Section: Introductionmentioning
confidence: 99%